2018
DOI: 10.1038/s41598-018-30874-z
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of psychosocial and lifestyle predictors of peripartum depressive symptoms associated with distinct risk trajectories: a prospective cohort study

Abstract: Perinatal depression involves interplay between individual chronic and acute disease burdens, biological and psychosocial environmental and behavioural factors. Here we explored the predictive potential of specific psycho-socio-demographic characteristics for antenatal and postpartum depression symptoms and contribution to severity scores on the Edinburgh Postnatal Depression Scale (EPDS) screening tool. We determined depression risk trajectories in 480 women that prospectively completed the EPDS during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…From this perspective, we, also, documented that lower education level, being unemployed, perceived stress in the last month and the presence of any recent life adversity raised the probability of suffering from depression during pregnancy as compared to postpartum. We, therefore, confirmed previous data reporting that stressful life events are strongly associated with antenatal depression [50,51]. With foreign mothers, in particular, we observed an increasing risk of depression when moving from pregnancy to the postpartum period, perhaps due to cultural and affective separation from a familiar support system that might be necessary especially after childbirth [52].…”
Section: Discussionsupporting
confidence: 91%
“…From this perspective, we, also, documented that lower education level, being unemployed, perceived stress in the last month and the presence of any recent life adversity raised the probability of suffering from depression during pregnancy as compared to postpartum. We, therefore, confirmed previous data reporting that stressful life events are strongly associated with antenatal depression [50,51]. With foreign mothers, in particular, we observed an increasing risk of depression when moving from pregnancy to the postpartum period, perhaps due to cultural and affective separation from a familiar support system that might be necessary especially after childbirth [52].…”
Section: Discussionsupporting
confidence: 91%
“…From this perspective, we, also, documented that lower education level, being unemployed, perceived stress in the last month and the presence of any recent life adversity raised the probability of suffering from depression during pregnancy as compared to postpartum. We, therefore, con rmed previous data reporting that stressful life events are strongly associated with antenatal depression [37]. With foreign mothers, in particular, we observed an increasing risk of depression when moving from pregnancy to the postpartum period, perhaps due to cultural and affective separation from a familiar support system that might be necessary especially after childbirth [38].…”
Section: Discussionsupporting
confidence: 90%
“… 40 , 41 Our data indicated a role for pregnancy stress, domestic violence, and depressive prenatal mood in PDSs. Consistent with a systematic review, 42 multivariate analysis showed that depressive prenatal mood was a strong predictor of PDSs, and the risk of PDSs in women with depressive prenatal mood during cesarean section was five times that of women with no prenatal depression. It also suggested that in addition to genetic factors that cannot be interfered with, we need to pay attention not only to the postpartum psychological and emotional state but also to understanding the prenatal psychological and emotional state.…”
Section: Discussionsupporting
confidence: 77%